The Role of the Binmas Unit in Reducing the Spread of Covid-19 in the Barelang Police Legal Area - Billy Pratama Putra (Advances in Police Science Research Journal, 2022)
This research was motivated by the high rate of spread of COVID-19 in the jurisdiction of the Police Resort Barelang. The role of the Binmas Unit in reducing the spread of COVID-19 in Batam City will be discussed in this study. In Article 13 of Law Number 2 of 2002, it is explained that the State Police of the Republic of Indonesia has main duties such as maintaining public security and order, upholding the law and providing protection, protection and services to the community. The research method uses a qualitative approach whose results are reinforced by the presence of findings, observations, document studies, and interviews with information sources. The techniques used for data analysis include data reduction, data presentation, and drawing conclusions. The results of the study found that the role of the Binmas Unit in reducing the spread of COVID-19 in Batam City was still not optimal, influenced by several internal factors and external factors including internal factors, namely human resources, budget, facilities and infrastructure, work methods and markets. As well as external factors including the economy and the lack of public awareness. Based on the results of the research, the authors suggest that the addition and placement of personnel according to competence and rank levels, optimize analysis and evaluation by Kasatbinmas, provide training education on counseling, equip officers with the ability to master audience and communication science And presumably the Police Resort Barelang Public Guidance Unit can provide sufficient inventory items to support the implementation of activities.